Simultaneous determination of seven acrylates in food contact paper products by GC/MS and modified QuEChERS. Issue 19 (3rd May 2016) - Xun, Zhiqing; Huang, Jinfeng; Li, Xiu-Ying; Lin, Senyu; He, Shuang; Guo, Xindong; Xian, Yanping
Abstract : A new method was established to determine acrylates in food contact paper products by utilizing modified QuEChERS technology and GC/MS. Abstract : By utilizing gas chromatography tandem mass spectrometry (GC/MS) and QuEChERS purification technology, a new method was developed for the detection of seven acrylate compounds (methyl methacrylate, butyl acrylate, sec -butyl acrylate, 2-ethylhexyl acrylate, glycidyl methacrylate, n -octyl acrylate, and N -octyl methacrylate) in food contact paper products. Hexane was used as the extraction solvent and carbon nanotubes were used as adsorbents during the QuEChERS purification. The acrylates were separated by an ultra-inert column (DB-5MS UI) and detected in the electron ionization mode of MS with selected ions monitoring (SIM). Under the optimal conditions, the calibration curves for the seven analytes were linear in the range of 5.0–1000 μg L −1 with the correlation coefficients higher than 0.9984. The quantitation limits of the method (S/N = 10) of these acrylates were in the range of 50.0–100.0 μg kg −1 . The mean recoveries for paper products at three spiked concentration levels of 50.0–1000 μg kg −1 were in the range of 82.1–106.5%, and the relative standard deviations (RSDs, n = 6) ranged from 1.5% to 5.6%. This method is accurate, simple and rapid, and could be applied to the detection of acrylates in food contact paper products.